PENGARUH CELEBRITY ENDORSER NCT 127 DALAM IKLAN NATURE REPUBLIC INDONESIA TERHADAP MINAT BELI MELALUI OFFICIAL STORE: Survei Terhadap Followers Instagram @naturerepublic.id - Adinda Zahwa Mayussa, (2022)
The number of South Korean cosmetic imports in Indonesia increases every year due to the Korean Wave phenomenon, including Nature Republic. This phenomenon causes the circulation of fake Nature Republic products through unofficial stores to increase, so Nature Republic Indonesia uses the celebrity endorser NCT 127 to foster buying interest through official store. This study aims to determine how much influence the celebrity endorser NCT 127 in the Nature Republic Indonesia advertisement has on purchase intention through official store. The theory used in this research is the cognitive response theory by Belch & Belch. The research methodology used is quantitative approach, explanatory type, and survey method. The population of this study are followers of the Instagram account @naturerepublic.id with a total sample of 100 respondents. The sampling technique used was non-probability sampling and purposive sampling technique with specified criteria. The technique of collecting data is through the distribution of questionnaires that have gone through the stages of validity and reliability testing. The data collected were analyzed using correlation test, simple linear regression test, coefficient of determination test, and hypothesis testing through the SPSS 25 program. Correlation test shows that the relevance between Variable X (Celebrity Endorser) to Variable Y (Purchase Interest) is strong. The results showed that the level of influence of Variable X (celebrity endorser) on Variable Y (buying interest) was 41.1%, then celebrity endorser NCT 127 has a great influence on consumer purchase intention. The results of the Hypothesis Test analysis state that the influence of Variable X (celebrity endorser) on Variable Y (Purchase Interest) has a large and significant effect.